Estimating thresholds of nitrogen, phosphorus and potassium fertilizer rates for rice cropping systems in China - Liu, Yingxia; Ding, Wencheng; He, Ping; Xu, Xinpeng; Zhou, Wei (Frontiers in Plant Science, 2024)
Determining the fertilization rate plays a pivotal role in agronomic practices as they directly impact yield targets, soil fertility, and environmental risks. In this study, we proposed a method that utilizes allowed ranges of partial nutrient balance and yield to estimate the threshold of nitrogen (N), phosphorus (P), and potassium (K) fertilizer applied to rice (Oryza sativa L.) fields in China. Based on a dataset of 6792 observations from rice fields, we determined the minimum and maximum rates of N, P and K suggested for single (mono-season rice), middle (summer-season rice rotated with winter-season upland crop), early and late (double-season rice cropping system) rice, ranging between 114−146 and 220−292 kg N ha−1 per season, 56−74 and 112−149 kg P2O5 ha−1 per season, and 170−230 and 329−347 kg K2O ha−1 per season, respectively. These values serve as the lower and upper fertilization thresholds, guiding yield goals and environmental protection. Furthermore, if rice straw is returned to fields, the demand for K fertilizer can theoretically decrease by 183 kg K2O ha−1, with corresponding decreases of 50 kg N ha−1 and 26 kg P2O5 ha−1, respectively. A recommended fertilization approach, excluding returned straw nutrients from the upper fertilization thresholds, suggested average application rates of 194 kg N ha−1, 105 kg P2O5 ha−1, and 157 kg K2O ha−1, which align well with the nutrient requirements of rice. Additionally, substituting organic N for chemical N is an effective approach to conserve chemical fertilizer N, potentially reducing chemical N usage by 20%−40%. Utilizing slow-release N is also a favorable option to enhance N use efficiency and optimize N balance. This study offers valuable insights into the development of fertilization restriction indicators, aiming to achieve a delicate balance between environmental impact and agricultural productivity through the adoption of balanced fertilization rates and utilization of organic residues.